Exposure to salinity induces oxidative damage and changes in the expression of genes related to appetite regulation in Nile tilapia (Oreochromis niloticus) - Martins, Amanda W. S.; Dellagostin, Eduardo N.; Blödorn, Eduardo B.; Silveira, Tony Leandro R.; Sampaio, Luis A.; Komninou, Eliza R.; Varela Junior, Antonio S.; Corcini, Carine D.; Nunes, Leandro S.; Remião, Mariana H.; Collares, Gilberto L.; Domingues, William B.; et al. (Frontiers in Genetics, 2022)
Variations in water salinity and other extrinsic factors have been shown to induce changes in feeding rhythms and growth in fish. However, it is unknown whether appetite-related hormones mediate these changes in Nile tilapia (Oreochromis niloticus), an important species for aquaculture in several countries. This study aimed to evaluate the expression of genes responsible for appetite regulation and genes related to metabolic and physiological changes in tilapia exposed to different salinities. Moreover, to sequence and characterize cart, cck, and pyy genes and quantify their expression in the brain and intestine of the fish by quantitative polymerase chain reaction (qPCR). The animals were exposed to three salinities: 0, 6, and 12 parts per thousand (ppt) salt for 21 days. Furthermore, lipid peroxidation, reactive oxygen species, DNA damage, and membrane fluidity in blood cells were quantified by flow cytometry. The results indicated an increased expression of cart, pyy, and cck and a decreased expression of npy in the brain, and the same with cck and npy in the intestine of fish treated with 12 ppt. This modulation and other adaptive responses may have contributed to the decrease in weight gain, specific growth rate, and final weight. In addition, we showed oxidative damage in blood cells resulting from increasing salinity. These results provide essential data on O. niloticus when exposed to high salinities that have never been described before and generate knowledge necessary for developing biotechnologies that may help improve the production of economically important farmed fish.